Empirical Investigation of Online Advertisement and Consumer Buying Intention in Restaurant Industry (Journal of Asian Development Studies, 2023)
This research aims to unravel the intricacies of factors impacting consumer buying intentions towards online advertisements. The study leans on a digital platform, deploying a survey disseminated through the Facebook group "SWOT" and garnering responses from approximately 195-200 participants of diverse ages and genders by using smart PLS to interpret the empirical data. Findings suggest that online advertising significantly affects consumer buying behavior within the restaurant industry. Factors such as perceived commercial reliability, communication demand, interactivity, and response toward ads have been pinpointed as substantial influencers on consumption patterns. Furthermore, the research also investigates the association between intent and behavior, unveiling nuanced insights into the participant's experiences and motivations to engage in online purchases. The insights derived from this study provide a foundational understanding for marketers and businesses in the restaurant industry to discern the pivotal role of online advertising in shaping consumer purchase intentions and satisfaction. It can serve as a guidepost to sculpt online advertising strategies, especially concerning customer engagement and communication.